2009
DOI: 10.1073/pnas.0908660107
|View full text |Cite
|
Sign up to set email alerts
|

Murine leukemia virus glycosylated Gag (gPr80 gag ) facilitates interferon-sensitive virus release through lipid rafts

Abstract: Murine leukemia viruses encode a unique form of Gag polyprotein, gPr80 gag or glyco-gag. Translation of this protein is initiated from full-length viral mRNA at an upstream initiation site in the same reading frame as Pr65 gag , the precursor for internal structural (Gag) proteins. Whereas gPr80 gag is evolutionarily conserved among gammaretroviruses, its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 34 publications
3
55
1
Order By: Relevance
“…Internal deletions of 9 nt similar to what we have identified in the CFS patients and the blood donors are known to be present in the region that encodes the glycosylated Gag protein (GlycoGag) in some infectious endogenous (ecotropic) MLVs and exogenous (xenotropic) MLVs, such as AKV and DG-75 (14,15). Many previous studies have shown that the nonstructural GlycoGag of MLVs plays a critical role in viral pathogenesis and in vivo infectivity (16)(17)(18)(19). In this context, the MLV-like virus gag gene sequences identified in most of our CFS patients (both CFS type 1 and CFS type 2) appear to have an intact GlycoGag inframe with the matrix and are consistent with the gene sequences of infectious MLVs.…”
Section: Discussionsupporting
confidence: 77%
“…Internal deletions of 9 nt similar to what we have identified in the CFS patients and the blood donors are known to be present in the region that encodes the glycosylated Gag protein (GlycoGag) in some infectious endogenous (ecotropic) MLVs and exogenous (xenotropic) MLVs, such as AKV and DG-75 (14,15). Many previous studies have shown that the nonstructural GlycoGag of MLVs plays a critical role in viral pathogenesis and in vivo infectivity (16)(17)(18)(19). In this context, the MLV-like virus gag gene sequences identified in most of our CFS patients (both CFS type 1 and CFS type 2) appear to have an intact GlycoGag inframe with the matrix and are consistent with the gene sequences of infectious MLVs.…”
Section: Discussionsupporting
confidence: 77%
“…Glyco-Gag is incorporated into MLV virions (4,14), and we found that glyco-Gag mutant viruses have less stable capsids. Although it is possible that capsid stability and resistance to restriction are unlinked, our data suggest that by increasing the stability of the capsid, glyco-Gag renders these viruses more Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Glyco-Gag mutant M-MLV buds differently from WT virus and contains less membrane cholesterol (13,14). To determine whether these changes affected stability of viral cores, we treated equal amounts of WT and glyco-Gag mutant virions isolated from NIH 3T3 cells with 0.5% Triton X-100, followed by sucrose density gradient centrifugation; the virion preparations contained the p30 CA only found in mature virions.…”
Section: Glyco-gag Mutant and Wt MLV Produced In Vivo Contains Apobec3mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms engaged by gPr80 to promote virus replication remain largely unknown. However, a recent report has revealed that gPr80 affects release of both MLV and HIV-1 by facilitating budding from lipid rafts (48).…”
mentioning
confidence: 99%